2020
DOI: 10.1186/s12978-020-00935-6
|View full text |Cite
|
Sign up to set email alerts
|

Perception and practices of menstruation restrictions among urban adolescent girls and women in Nepal: a cross-sectional survey

Abstract: Background: Menstruation, a natural biologic process is associated with restrictions and superstitious beliefs in Nepal. However, factual data on women's perspectives on menstrual practices and restrictions are scarce. This study aimed to assess socio-cultural perceptions of menstrual restrictions among urban Nepalese women in the Kathmandu valley. Methods: Using a clustered random sampling, 1342 adolescent girls and women of menstruating age (≥15 years) from three urban districts in the Kathmandu valley compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 17 publications
4
64
0
Order By: Relevance
“…The use of unhygienic clothes to replace pads or tampons may cause restriction in movement, skin irritation, concerns about leaking and odor [ 8 , 9 ], and increase the risk of urogenital infections [ 10 , 11 ]. In Nepal, many families impose restrictions on menstruating girls and women, which may vary based on religion, social group and education level [ 12 ]. The severest restriction is "Chhaupadi", meaning the isolation of menstruating women in small huts made of mud and stones with no doors or windows, which is still practiced in the Far-Western Development Region of Nepal [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of unhygienic clothes to replace pads or tampons may cause restriction in movement, skin irritation, concerns about leaking and odor [ 8 , 9 ], and increase the risk of urogenital infections [ 10 , 11 ]. In Nepal, many families impose restrictions on menstruating girls and women, which may vary based on religion, social group and education level [ 12 ]. The severest restriction is "Chhaupadi", meaning the isolation of menstruating women in small huts made of mud and stones with no doors or windows, which is still practiced in the Far-Western Development Region of Nepal [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…14 A recent study byAmrita Mukherjee and team in 2020, found that 45.5% of the total participants (n=1342) saw menstruation as a bother or curse, 66.1% purify the kitchen, bed, bedsheets, or other household things on the fourth days and 72.1% were encouraged by their mothers to practice the restrictions. 15 Now, it is not only the problem of the developing world, it is believed to exist globally. However, the data are scarce.…”
Section: Impact Of Menstrual Restriction On Healthmentioning
confidence: 99%
“…South Asian countries, in particular, have been noted for the depth of restrictions surrounding limitations in types of food, rules on which cultural/religious events menstruating females may attend, and who they may interact with/near [11]. Such restrictions are deeply rooted in the traditional beliefs and teaching of Hindu culture, which possess strong superstitions surrounding the impurity of blood [12].…”
Section: Introductionmentioning
confidence: 99%